"تقدير دوال السلوكية الكلية و نماذج التوازن العام في الجزائر دراسة قياسية خلال الفترة (1980-2019)" - محمد المشري, التجاني (University of eloued جامعة الوادي, 2020)
كان الهدف من هذه الدراسة تحديد المتغيرات الاقتصادية الكلية المحددة للسلوك الاقتصادي لمتغيرات الاستهلاك للقطاع العائلي والسلوك الاستثماري لقطاع الأعمال وكذا سلوك الواردات ضمن قطاع العالم الخارجي، ومن ثمّ نمذجة معادلة التوازن العام للاقتصاد الجزائري الذي يتحدد من خلال التوازن الآني في سوق السلع والخدمات وسوق النقد. وقد خلصت الدراسة إلى أن الناتج المحلي الإجمالي يُعتبر أهم محدد لسلوك الاستهلاك والاستثمار والواردات. في حين تُؤثر معدلات الفائدة عكسيا في الاستثمار. أما التوازن العام فيتحدد من خلال مكونات الطلب الكلي.Abstract: The aim of this study was to determine the specific macroeconomic variables of the economic behavior of the consumption variables of the family sector, the investment behavior of the business sector, as well as the behavior of imports within the external world sector, and then modeling the general equilibrium equation for the Algerian economy, which is determined by the instantaneous equilibrium in the market for goods and services and the money market. The study concluded that GDP is the most important determinant of consumption, investment and import behaviour. Whereas, interest rates adversely affect investment. The general equilibrium is determined by the components of aggregate demand.
مذكرة ماستر اقتصاد كمي
Keywords: استهلاك، استثمار، واردات، توازن سوق السلع والخدمات وسوق النقد.; consumption, investment, imports, market equilibrium of goods and services and money market.